The Effect of Work Culture and Work Discipline on Performance of Education Services Office of North Luwu District - Wasmiana Wasmiana; Muh. Yusuf Qamaruddin; Sapar Sapar (Institute of Computer Science (IOCS), 2021)
This study is a study that examines the influence of work culture and work discipline on employee performance at the District Education Office. North Luwu. The research model is Multiple Linear Regression Analysis. With primary data, using a questionnaire. A total of 98 samples were determined in this study. The results of the study are that work culture has a positive and significant impact on the performance of the employees of the District Education Office. North Luwu. Work discipline also has a positive and significant effect on the performance of the employees of the District Education Office. North Luwu. Simultaneously, work culture and work discipline have a significant influence on the performance of the employees of the District Education Office. North Luwu.